Minimal Energy Path Planning for Wireless Robots - Ooi, Chia Ching; Schindelhauer, Christian (Mobile Networks and Applications (MONET))

Utilizing detours for energy conservation in mobile wireless networks - Ooi, Chia Ching; Schindelhauer, Christian (Telecommunication Systems)

Towards an EU Directive on Protected Funds / National Report for Germany - Krimphove, Dieter (Towards an EU Directive on Protected Funds: Law of Business and Finance)

Colouring Non-sparse Random Intersection Graphs - Raptopoulos, Christoforos L.; Nikoletseas, Sotiris E.; Spirakis, Paul G. (34st International Symposium on Mathematical Foundations of Computer Science)

Combinatorial Properties for Efficient Communication in Distributed Networks with Local Interactions - Nikoletseas, Sotiris E.; Raptopoulos, Christoforos L.; Spirakis, Paul G. (Proceedings of IPDPS - IEEE International Parallel & Distributed Processing Symposium)

Ästhetisch-biografische Arbeit und ihre Relevanz für die Professionalisierung der LehrerInnenbildung. Habilitationsvortrag an der Bergischen Universität Wuppertal - Büker, Petra
Mai 2009

Distributed Heterogeneous Hashing and Deterministic Dynamical Decompositions - Deveci, Deniz; Kortenjan, Michael; Schomaker, Gunnar (Parallel and Distributed Computing and Systems, Nr. 21)

Gefühltes Recht – Über die hirnorganische Evolution von Recht - Krimphove, Dieter (Rechtstheorie)

Auskunft, Information und Beratung im Bankgeschäft - Krimphove, Dieter (Finanzdienstleistungen für den Mittelstand)

Europäisches Religions- und Weltanschauungsrecht - Krimphove, Dieter (EuR Europarecht)

Verfahren und Gerechtigkeit: Gedanken zur Ökonomik von Streitentscheidungsverfahren - Krimphove, Dieter (Festschrift für Manfred Straube)

Analysis and implementation of an Artificial Homeostatic Hormone System: A first case study in robotic hardware - Stradner, Jürgen; Hamann, Heiko; Schmickl, Thomas; Crailsheim, Karl (2009 IEEE/RSJ International Conference on Intelligent Robots and Systems)
One of the prominent challenges in mobile robotics is to develop control methodologies that allow the adaptation to dynamic and unforeseen environments. The classic approach of hand-coded controllers is very efficient for well-defined tasks and specific environments but poor in adapting to changing environmental conditions. One alternative approach is the application of evolutionary algorithms which need, in turn, easily evolvable representations of controllers. In this paper, we investigate one promising approach of an artificial hormone system as a control paradigm which is believed to be easily optimized by evolutionary processes. In a first step of this research, we focus on the simple task of collision avoidance. We present a brief mathematical analysis of this controller approach and an implementation of the controller on a mobile robot to check the feasibility in principle of our approach. The task is successfully accomplished and we conclude with a discussion of the hormone dynamics in the robot.

Two different approaches to a macroscopic model of a bio-inspired robotic swarm - Schmickl, Thomas; Hamann, Heiko; Wörn, Heinz; Crailsheim, Karl (Robotics and Autonomous Systems)
By compiling macroscopic models we analyze the adaptive behavior in a swarm of autonomous robots generated by a bio-inspired, distributed control algorithm. We developed two macroscopic models by taking two different perspectives: A Stock & Flow model, which is simple to implement and fast to simulate, and a spatially resolved model based on diffusion processes. These two models were compared concerning their prediction quality and their analytical power: One model allowed easy identification of the major feedback loops governing the swarm behavior. The other model allowed analysis of the expected shapes and positions of observable robot clusters. We found a high correlation in the challenges posed by both modeling techniques and we highlighted the inherent problems of inferring emergent macroscopic rules from a microscopic description of swarm behavior.

Pattern Formation as a Transient Phenomenon in the Nonlinear Dynamics of a Multi-Agent System - Hamann, Heiko; Troch, Inge; Breitenecker, F. (MATHMOD 2009 - 6th Vienna International Conference on Mathematical Modelling)

Editorial Preface - Kundisch, Dennis

Strukturierter Entwurf selbstoptimierender mechatronischer Systeme - Oberschelp, Oliver

Verfahren zur strukturierten Vorausschau in globalen Umfeldern produzierender Unternehmen - Stollt, Guido

Methode zur zukunftsorientierten Entwicklung und Umsetzung von Strategieoptionen unter Berücksichtigung des antizipierten Wettbewerbsverhaltens - Wenzelmann, Christoph

Einsatz der Bibliometrie für das Technologiemanagement - Brüseke, Ute

Ein Verfahren zur hierarchischen Struktur-, Dimensions- und Material- bedarfsplanung von Fertigungssystemen - Timm, Thorsten